1998
DOI: 10.1086/306527
|View full text |Cite
|
Sign up to set email alerts
|

The Structure and Emission of the Accretion Shock in T Tauri Stars

Abstract: We have examined one of the key predictions of the magnetospheric infall model for classical T Tauri stars (CTTS), namely, the formation of a shock on the stellar surface. We Ðnd that accretion column emission can successfully reproduce the main observational properties of the excess continuum that veils the absorption features in CTTS. This success adds further support to the magnetospheric infall model for disk accretion. We have calculated the structure and the spectral energy distribution of the emergent c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
450
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 552 publications
(476 citation statements)
references
References 33 publications
25
450
1
Order By: Relevance
“…This velocity is an upper limit as the material starts only at the inner border of the circumstellar disk, probably following curved magnetic field lines down toward the star; a more realistic terminal speed is v m ≈ 0.8v ff (Calvet & Gullbring 1998). Upon braking at the stellar surface, a shock develops which, according to the strong-shock theory, reaches a temperature of T s = 3 16k m p μv 2 m ≈ 3.5 × 10 6 M M R R −1…”
Section: -P23mentioning
confidence: 97%
See 1 more Smart Citation
“…This velocity is an upper limit as the material starts only at the inner border of the circumstellar disk, probably following curved magnetic field lines down toward the star; a more realistic terminal speed is v m ≈ 0.8v ff (Calvet & Gullbring 1998). Upon braking at the stellar surface, a shock develops which, according to the strong-shock theory, reaches a temperature of T s = 3 16k m p μv 2 m ≈ 3.5 × 10 6 M M R R −1…”
Section: -P23mentioning
confidence: 97%
“…Such electron temperatures should therefore produce soft Xray radiation. The bulk of the ensuing X-rays are probably absorbed in the shock, contributing to its heating, although part of the X-rays may escape and heat the pre-shock gas (Calvet & Gullbring 1998); suggestive evidence for accretion-related X-ray production is available in the very soft X-ray range (e.g., based on flux excess in the O vii and Ne ix line triplets or indications of very high densities; Kastner et al 2002).…”
Section: -P23mentioning
confidence: 99%
“…The equivalent widths of spectral lines can be underestimated by excess continuum emission due to mass accretion activity (Calvet & Gullbring 1998;Lim et al 2014a ) were measured by integrating the observed emission lines. In the case of the He I line, we computed the equivalent width of the line core within a narrow wavelength range of 0.7 Å to minimize the contribution of the error in the continuum level.…”
Section: The Effect Of Veiling On the LI L6708 Linementioning
confidence: 99%
“…It is confirmed that a total of 27 stars have either a broad Hα emission line or a He I emission line, or both. If the spectral lines are veiled by accretion activities, l W 6708 (Li) may (Calvet & Gullbring 1998), and the lifetime of hot spots created by the accreted materials may also be different for a different accretion rate. The intensive time series observations of some PMS stars in NGC 2264 show aperiodic or periodic brightening events in their light curves on a timescale of several hours to 30 days (Stauffer et al 2014(Stauffer et al , 2016.…”
Section: The Effect Of Veiling On the LI L6708 Linementioning
confidence: 99%
“…This velocity is an upper limit as the material starts only at the inner border of the disk; a more realistic terminal speed is v m ≈ 0.8v ff (Calvet and Gullbring 1998). On the stellar surface, a shock develops with a temperature of…”
Section: Accretion-induced X-raysmentioning
confidence: 99%